Hall effect and magnetic ordering in RB12 - Baranovskiy, A.E.; Grechnev, G.E.; Shitsevalova, N.Yu.; Sluchanko, D.N.; Glushkov, V.V.; Demishev, S.V.; Sluchanko, N.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The concentration of carriers in LuB12 is evaluated theoretically by applying ab initio FP-LMTO calculations. Theoretical results are found to be in agreement with high precision measurements of the Hall RH(T) coefficient which were carried out on single crystals of the rare earth dodecaborides RB12 (R = Ho, Er, Tm, Lu) at temperatures 1.8–300 K. A nature of the antiferromagnetic ordering in RB12 is investigated within the RKKY-like model, which was supplemented by comprehensive electronic structure calculations for paramagnetic, ferromagnetic and antiferromagnetic phases.